Comparison of Gleptosil with iron Dextran for anemia prevention in young pigs - D S Pollmann; J E Smith; Jeffrey S Stevenson; D A Schoneweis; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1982)
Gleptosil, a commercial iron product, was compared with iron dextran for the prevention of iron deficiency anemia in young pigs. Using 26 litters, pigs (within each litter) were randomly allotted to one of the three treatments: 1) control (no iron), 2) iron dextran (200 mg) and 3) Gleptosil (2OO mg). Blood was collected at 0, 10, 21 and 50 days post-treatment for red blood cell count (RBC), hematocrit (HCT), hemoglobin (HGB) concentration, serum iron concentration and serum iron-binding capacity (IBC). At 21 days, 30 pigs (one pig/treatment from each of 10 litters) were killed to determine mg non-heme iron (NHFe) in liver and spleen, bile IBC and concentrations of bile and fecal iron. There were no differences (P<.05) between iron sources in 3- or 8-week body weight or in any of the blood or tissue characteristics. In contrast, control pigs gained less (P<.05) weight and had lower (P<.05) RBC, HGB, HCT, serum iron, and liver and spleen NHFe than those that received iron dextran or Gleptosil. Serum IBC was greater (P<.05) for the control than for iron-treated pigs. These results demonstrate that the iron from iron dextran and Gleptosil can be used with similar efficiency for anemia prevention in young pigs.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Gleptosil; Iron Dextran; Anemia; Young pigs